Mitochondrial subtypes in renal ischemia reperfusion injury guide delayed graft function and Long-Term graft prediction - Danni Hu; Zheng Wang (Scientific Reports)
Abstract Background Ischemia reperfusion injury (IRI) in kidney transplantation (KTx) is closely associated with acute rejection, delayed graft function (DGF), and graft failure. Evidence highlights the significant correlation between mitochondrial dysfunction and IRI. However, there is a scarcity of predictive models for DGF and long-term graft survival specifically focused on mitochondrial-related genes (MGs). Methods RNA-seq and Microarray datasets from the GEO database were utilized. Differential expression analysis identified differentially expressed MGs (DE-MGs), and consensus clustering analysis performed cluster analysis of IRI samples. Comprehensive bioinformatics methods and machine learning were applied to establish predictive models for DGF and long-term graft survival based on DE-MGs. Additionally, scRNA-seq was used for further analysis of the DE-MGs. Results Our study identified two IRI clusters (C1 and C2) with distinct molecular features and clinical characteristics. C1 represented an inflammation and immune-activated subtype with a higher incidence of DGF, whereas C2 exhibited active metabolism and a lower DGF incidence. Moreover, utilizing DE-MGs, we developed reliable predictive models for DGF and long-term graft survival. Additionally, we observed that DE-MGs were predominantly expressed in mast cells and found their crucial role in the cell communication networks by activation of AREG-EGFR, CSF1-CSF1R, NAMPT-INSR, and CTSG-PARD3 receptor-ligand pairs in KTx. Conclusion This study identified two distinct IRI clusters and developed powerful prediction models for DGF and long-term graft survival using DE-MGs. Additionally, it highlighted the crucial role of mast cells in KTx. These findings have implications for early prevention and customized therapy of postoperative complications in KTx.